THE REACTION OF MICE LYMPHOID ORGANS ON PEPTIDOGLYCAN OF STAPHYLOCOCCUS AUREUS WOOD 46 IN NORM AND UNDER TUMOR GROWTH - В. В. Позур; Л. М. Сківка; Г. П. Потебня (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2007)
The effects of peptidoglycan (PG) of Staphylococcus aureus wood 46 on the weight indexes and the cellularity of lymphoid organs in normal mice and mice with Lewis lung carcinoma were investigated. It was shown, that most immunogenic doze of PG both for intact animals, and for animals with experimental tumors was 2 μg/g though character of reaction of immune system organs on PG introduction in healthy mice and tumor bearing mice was different. Unlike healthy mice PG had no effect on thymus weight and relative amount of lymphocytes in mice with Lewis lung carcinoma. In addition in tumor bearing mice the reaction on PG administration was more significant. It is necessary to note that under the tumor growth dose-dependence of PG of Staphylococcus aureus wood 46 on studied lymphoid organs was observed in the number of cases.